Forensic Medicine Perspective on Eye Trauma: The Case of Balıkesir Province - Can, Hümeyra Yıldırım; Cengiz, Meksel; Can, Muhammet (The Bulletin of Legal Medicine, 2023)
Objective: General forensic examination and reporting after trauma due to forensic events is important. It is aimed to evaluate the general forensic examination reports prepared for forensic eye injuries due to trauma in our region, taking into account penal law. Methods: In the study, the medical records of 8.651 cases who applied to the Forensic Medicine Department for the preparation of forensic reports in the 6-year period between January 2016 and February 2022 were retrospectively analyzed. Eye injury was detected in 146 of the cases. Results: According to years, 8 (5.5%) cases were 2016, 17 (11.6%) 2017, 23 (15.8%) 2018, 24 (16.4%) 2019, 18 (12.3%) 2020, 48 (32.9%) of 2021 and 8 (5.5%) of them belonged to January and February of 2022. Thirty seven (25.3%) of 146 cases about whom a report was made were female and 109 (74.7%) were male. The male/female ratio (109/37) was found to be 2.94. Considering age groups of the cases; 87 (59.6%) cases, 25 female and 62 male, aged 20-49, 2 female and 13 male, total 15 (10.3%) cases aged 10-19, and aged 0-9 years. A total of 3 (2.1%) cases were detected, 1 female and 2 male. There was no significant relationship between age groups and gender. Conclusion: In addition to general forensic examination reports, various difficulties are encountered in the evaluation of forensic eye injury cases. It was concluded that ophthalmologists and forensic medicine specialists should work together in forensic eye injuries, as in many branches, in the preparation of forensic reports.